Quantitative validation of Ames IR intensity and new line lists for 32/33/34S16O2, 32S18O2 and 16O32S18O. (March 2019) - Huang, Xinchuan; Schwenke, David W.; Lee, Timothy J.
Highlights: First quantitative validation for the dipole moment surface adopted in Ames-296K SO2 IR intensity calculations, which integrates variational line lists and effective Hamiltonian and effective dipole model approaches. Systematic check on the reliability and convergence of vibrational dependence of effective dipole of 13 SO2 vibrational states. Partition Sum convergence check at 296 K along J and E'. Isotopologue consistency is superior relative to regular effective dipole models. Combine the high quality Ames IR intensity with the reliable high-resolution experimental line positions or rovibrational energy levels. Provide three sets of IR lists for 5 SO2 isotopologues, the best available alternative for SO2 high-resolution IR database updates Abstract: The quality of Ames-296K SO2 Infrared (IR) line list intensities is first validated by quantitative exploration of several dipole moment surfaces (DMSs) and partition sum convergence. The DMSs are computed with several of Dunning's correlation-consistent basis sets and their vibrational dependence are compared to the empirical model derived from Stark effect experiments reported by D. Patel, D. Margolese, and T.R. Dyke [ J. Chem. Phys. 70, 2740 (1979)]. The effective dipole deviations from the DMS adopted in the Ames IR lists is 0.2–0.4% for vibrational states up to 3ν3 . The vibrational dependence of the dipole moment is also in good agreement, except for n ν1 . Partition sum convergence at 296 K is confirmed by new calculations with rotational quantum number J up to 150 and upper state E' up to 8000 cm −1 . The isotopologue consistency of the Ames IR line lists is superior relative to the regular Effective Hamiltonian (EH) models and Effective Dipole Moment (EDM) models. The ν1  + ν2 and ν2  + ν3 intensity consistency check reveals the recently reported experimental intensities need significant improvement or re-analysis. After the accuracy, convergence, and isotopologue consistency have been confirmed, the theoretical Ames-296K intensities are combined with the experimental line positions or EH models that experimental spectroscopists published after 2009. Three high-resolution IR line sets are reported for the 32/33/34 S 16 O2, 32 S 18 O2 and 16 O 32 S 18 O isotopologues: (1) the "New Lines Sets" include experimentally measured line positions; (2) the "Expanded Line Sets" include possible transitions among new rovibrational levels assigned in experiments and ground state (GS) levels predicted by reliable EH models; (3) the "Ames + MARVEL Sets" include possible transitions among all those levels reported in a recent MARVEL analysis. [Tóbiás et al, JQSRT208, 152 (2018)]. Compared to the limited data in High-resolution TRANsmission molecular absorption database (HITRAN), these line sets have significantly improved the data coverage up to 4000 cm −1 . Some missing bands can be traced to the unpublished experimental data. The isotopologue consistency of these line sets will help identify the uncertainties and defects in the experimental EH and EDM models. These line sets are good candidates for the next HITRAN update, if line shape parameters are available. The line sets can be downloaded from supplementary files or from the Ames Molecular Spectroscopic Database athttp://huang.seti.org .